STRATEGI PROMOSI FOOD AND BEVERAGE DALAM MENARIK MINAT TAMU DI HOTEL EMERALD GARDEN INTERNATIONAL MEDAN - Zalukhu, Martaria Silviani; Arief, Andi M Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the implementation and inhibiting factors of food and beverage promotion strategies in attracting guests at the Emerald Garden International Hotel Medan based on the marketing mix theory by Philip Kotler namely, Advertising, Personal Sales, Public Relations, Direct Marking and Sales Promotion. Food and beverage department is a department that is absolutely necessary in the hotel in the supply and service of food and beverages. This research uses descriptive qualitative research methods. The promotion strategy used at the Emerald Garden Hotel has been effective when viewed from the perceptions of visiting guests. According to the marketing manager the most effective strategy is through electronic media and social media by advertising and creating food events with attractive variants and discounts that satisfy guests. Then the number of guest respondents chosen randomly from this study was 30 guests, which aims to determine the level of success of the promotion of food and beverage strategies at the Emerald Garden hotel where guests have at least once tried food and beverage at the Emerald Garden International Hotel Medan Hotel. Data collection techniques in this study used observation, questionnaires, questionnaires, interviews and documentation. Based on research conducted, the results of data processing show the success rate of food and beverage promotion strategies in attracting guests' interest at the Emerald Garden International Hotel Medan can be said to be successful. Keywords: Promotion Strategy, Food and Beverage, Implementation, Advertising, and Success Level.